Suppression of recombination in waveguide in c-plane InGaN-based green laser diodes. (November 2017) - Cheng, Yang; Liu, Jianping; Zhang, Liqun; Jiang, Desheng; Tian, Aiqin; Zhang, Feng; Feng, Meixin; Wen, Pengyan; Zhou, Wei; Zhang, Shuming; Ikeda, Masao; Li, Deyao; et al.
Abstract: Recombination in InGaN upper waveguide in c-plane InGaN-based green laser diodes (LDs) has been investigated by both simulation and experiments. It is found that a potential barrier located at the interface between GaN last barrier and InGaN upper waveguide layer causes strong recombination in InGaN upper waveguide layer and lowers the carrier injection efficiency of InGaN-based green LDs when In content is higher than 4%. A suitable reduction of indium content in InGaN upper waveguide layer can effectively suppress recombination in waveguide and thus reduce the threshold current of green LDs. Highlights: The recombination in InGaN upper waveguide layer was investigated by both simulation and experiments. The origin of recombination in InGaN upper waveguide layer has been found. The effective method to suppress recombination in InGaN upper waveguide layer has been found.